Caribbean financial statistics (volume 2 - June 1998) : factbook of the securities markets of the Caribbean Community (The Centre St. AugustineTT, 1998)
Covers the regional stock exchanges of Barbados, Jamaica and Trinidad and Tobago over the period 1993-1997. Tracks the activity in the trading of treasury bills and government bonds issued in the Bahamas, Barbados, Belize, Eastern Caribbean States, Guyana, Jamaica, Suriname and Trinidad and Tobago from 1975 to 1997. Includes the operating results of a cross-section of the existing mutual funds in the region.
DC